Photographing waterdrops : exploring macro worlds with Harold Davis - Davis, Harold, 1953- (Waltham, Mass. : Focal Press, 2012)
"How to shoot waterdrops with a macro lens"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Macrophotography; Photography of water; Drops -- Pictorial works; Electronic books